Molecular Isolation and Identification of Multidrug-resistant Escherichia coli from Milk, Meat, and Product Samples - Dowidar , Heba A.; Khalifa, Marwa I. (Journal of Advanced Veterinary Research, 2023)
Pathogens can acquire resistance to antimicrobials used in veterinary and medical fields. Such pathogens can be found in several dietary and environmental sources. As Gram-negative infections in humans are most frequently caused by Escherichia coli (E. coli), antibiotic resistance in this organism is particularly concerning. This investigation was carried out to ascertain the antibiotic sensitivity profile of E. coli isolated from various food products randomly gathered from Egypt. To extract E. coli and examine its pattern of antibiotic susceptibility, 100 samples of raw milk, karish cheese, ground beef, and beef were bacteriologically processed. In the current study, E. coli strains were detected at a high frequency of 40% in raw milk, 28% in Karish cheese, 16% in ground beef, and 8% in beef. E. coli was isolated from 23% of milk, meat, and product samples. The 16S rRNA gene was detected using polymerase chain reaction (PCR) to confirm E. coli strains. The isolates of E. coli with the greatest percentages of multidrug-resistant (MDR) were tetracycline (26%), ampicillin (21.7%), streptomycin and sulfamethoxazole-trimethoprim (17.3%), cefotaxime, kanamycin and ceftazidime (13 %). The total occurrence of MDR E. coli was 34.7%. Pathogen cycling in food is common and may endanger the consumer’s health. To avoid this entirely, good hygiene practices for dairy farms and abattoirs are essential for preventing contamination of milk, meat, and product samples.